Dermoscopy of small melanomas: just miniaturized dermoscopy?. (11th June 2014) - Seidenari, S.; Ferrari, C.; Borsari, S.; Fabiano, A.; Bassoli, S.; Giusti, F.; Ponti, G.; Magnoni, C.
Abstract : What's already known about this topic? Only sporadic reports on the dermoscopic aspects of small melanomas are available at present. As small melanomas are those in an initial growth phase, it is important to know whether they have peculiar dermoscopic features enabling early diagnosis. What does this study add? To the best of our knowledge, this article presents the largest dermoscopic database on small melanomas and micromelanomas. Summary: Background: Small malignant melanomas (MMs) are usually MMs in an initial growth phase, deserving attention by the clinician aiming at an early diagnosis. Objectives: To identify clues for early diagnosis of small MMs, by comparing the dermoscopic features of MMs < 4 mm (micromelanomas) with those of larger MMs. Methods: Our database consists of dermoscopic images of 482 MMs, which have been retrieved and measured digitally. The ABCD (asymmetry, border, colour, dimension) and 7‐point criteria were evaluated for the whole database by three expert dermoscopists, whereas the main dermoscopic pattern was assessed only for micromelanomas. The dermoscopic aspects were correlated to clinical and histological features. Results: Most 7‐point and ABCD scores, and criteria referring to micromelanomas, differed from those of the MM database as a whole. Lesion asymmetry, number of colours, blue–whitish veil, atypical vessels, irregular globules/dots and regression increased according to MM diameter. An inverse trend was observed for atypical network and irregular pigmentation, which were more frequently observed in micromelanomas than in larger ones. Among the 22 micromelanomas, 12 lesions were in situ, whereas the other 10 were 0·2–2 mm thick. The clinical and dermoscopic characteristics of the two groups were similar. Conclusions: Micromelanomas are not a rarity. However, the clinician should be aware of the fact that the majority of them lack most of the dermoscopic features presented by larger lesions.